2016
DOI: 10.18632/oncotarget.12374
|View full text |Cite
|
Sign up to set email alerts
|

JWA down-regulates HER2 expression via c-Cbl and induces lapatinib resistance in human gastric cancer cells

Abstract: Human epidermal growth factor receptor 2 (HER2) targeted therapy is currently considered as the standard treatment for HER2-positive advanced gastric cancer (GC). However, unsatisfactory results of recent phase III clinical trials involving lapatinib suggested biomarkers for selection of patients. The aim of this study was to identify JWA as a biomarker for lapatinib resistance in GC cells and elucidate the underlying mechanisms. Lapatinib was effective to the intrinsic cisplatin-resistant GC cells. JWA activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 30 publications
(34 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have reported that the HER family receptors are degraded with a help of their specific ubiquitin ligases [21] , [22] . For example, HER1 is degraded by ubiquitin ligase c-Cbl [23] , HER2 is mediated by c-Cbl [24] , [25] , [26] or chaperon-interacting protein (CHIP) [27] , [28] . HER4 is ubiquitinated by WWP1 [32] or Itch [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the HER family receptors are degraded with a help of their specific ubiquitin ligases [21] , [22] . For example, HER1 is degraded by ubiquitin ligase c-Cbl [23] , HER2 is mediated by c-Cbl [24] , [25] , [26] or chaperon-interacting protein (CHIP) [27] , [28] . HER4 is ubiquitinated by WWP1 [32] or Itch [33] .…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study reported that JWA (adenosine diphophate-ribosylation-like factor 6 interacting protein 5, ARL6ip5) reversed cisplatin resistance in human GC 59 , whereas lower expression of JWA sensitized cisplatinresistant GC cells to lapatinib-induced apoptosis 32 . Collectively, these three studies have led to the proposals for some significant therapy regimens in GC patients: higher expression of JWA may be used as a biomarker for cisplatin treatment, lower expression of JWA may be utilized to identify patients that would benefit from HER2targeted therapy; in terms of the anti-angiogenesis therapy, silencing of circRACGAP1 may be a potential intervention strategy to reduce the toxicities and promote the antitumor effect of apatinib.…”
Section: Discussionmentioning
confidence: 99%
“…Western blotting and immunohistochemical staining were performed as previously described 32 . The antibodies used were as follows: monoclonal anti-GAPDH (loading control) (1:1000, Beyotime, Haimen, Jiangsu, China) and monoclonal anti-LC3B, SQSTM1, ATG7, and VEGFR-2 (1: 1000, Cell Signaling Technology, Danvers, MA, USA).…”
Section: Western Blotting Immunohistochemical Staining and Antibodiesmentioning
confidence: 99%
“…Patients with lower expression of JWA in tumor tissues usually suffer worse survival than those with higher expression [15,16]. JWA negatively regulates HER2 expression and inhibits cell proliferation and migration in human GC cells through transcription and ubiquitination related mechanisms [17,18]. However, the role of JWA in regulating HER2 expression and its underlying mechanism in BC have not been determined.…”
Section: Introductionmentioning
confidence: 99%